A Defective Nanotube Molecule of C552H496N24 with Pyridinic and Pyrrolic Nitrogen Atoms. (25th November 2021) - Ikemoto, Koki; Harada, Shotaro; Yang, Seungmin; Matsuno, Taisuke; Isobe, Hiroyuki
Abstract: A 3‐nm molecule comprising a cylindrical core and cross‐shaped rims was designed and synthesized by developing a modular synthetic route. By using a cyclic precursor from previous studies as a starting material, multiple carbazole units were installed at the rims of the defective cylinder. The defective cylinder was synthetically doped with two types of nitrogen atoms, that is, pyridinic and pyrrolic nitrogen atoms, which resulted in solvatochromic shifts in fluorescence by charge‐transfer interactions. The structure of the large, C552 H496 N24 molecule was fully disclosed by crystallographic analyses, and the unique helical arrangement of nitrogen‐doped cylinders in the crystal was revealed. Abstract : A gigantic molecule composed of 1072 atoms was designed and synthesized to install two types of nitrogen dopants in a defective nanotube molecule. Charge‐transfer interactions originating from the pyridinic and pyrrolic nitrogen dopants were disclosed by solution‐phase analyses, and 3‐nm molecular structures and a unique helical assembly were revealed by crystallographic analyses.